1965
DOI: 10.1172/jci105285
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin changes in disease: quantitation on the basis of heavy polypeptide chains, IgG (gammaG), IgA (gammaA), and IgM (gammaM), and of light polypeptide chains, type K (I) and type L (II).

Abstract: The immunoglobulins are made up of heavy and light polypeptide chains (1, 2). There are three major classes of immunoglobulin (gamma globulins) that are commonly identified in normal human serum: the IgG (yG-, or 7 S y2-globulin), the IgA (yA-, ylA-, or /32A-globulin), and the IgM (yM-, YlM-, 12M-, or 18 S -yi-macroglobulin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

1966
1966
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(15 citation statements)
references
References 29 publications
3
11
0
1
Order By: Relevance
“…The kappa: lambda ratios obtained in this study are significantly higher than normal values previously reported, but are similar to those observed in similar diseases (2). The average serum kappa: lambda ratio for the group as a whole was 3.74.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The kappa: lambda ratios obtained in this study are significantly higher than normal values previously reported, but are similar to those observed in similar diseases (2). The average serum kappa: lambda ratio for the group as a whole was 3.74.…”
Section: Introductionsupporting
confidence: 86%
“…The light chains are divided into two major antigenic types, Type-I or kappa and Type II or lambda. Circulating IgG contains types kappa and lambda in approximately a 2: 1 ratio (kappa: lambda) (1,2), and specific antibodies also contain both types in varying ratios (3).…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study clearly show that the in vivo and in vitro labeled G3 are metabolized similarly ( Fig. 1) In IgG-myeloma patients the concentration of nonmyeloma IgG is usually decreased (20,21 (Fig. 2).…”
Section: Resultsmentioning
confidence: 56%
“…As the disease progres ses, patients with Hodgkin's disease may become lymphopenic and their circulating lymphocytes have been shown to respond poorly to stimulation with phytohemagglutinin (187)(188)(189). On the other hand, circulating immuno globulins are usua i ly normal and antibody responsiveness may be normal as well (190)(191)(192)(193)(194)(195)(196)(197)(198). However, primary antibody responses to certain antigens may be less vigorous than normal, a finding very similar to that of neonatally thymectomized animals.…”
Section: Immunological Diseases Involving Primarily the Thymus Systemmentioning
confidence: 99%